KINERJA KEUANGAN, NILAI PERUSAHAAN: CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Hardianti, Vitria; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the impact of the disclosure of corporate social responsibility and good corporate governance on the influence of financial performance to the firm value. In this research, good corporate governance is measured by using proxy is managerial ownership (KM) and Independent commisioner (KI). The fianncial performance is measured by using proxy return on asset (ROA). Meanwhile, firm value is measured by using price book value (PBV).In this research, the sample collection technique has been determined by using purposive sampling, and based on the determined criteria the amount of observations are 23 manufacturing companies in the basic industries and chemicals sector which are listed in Indonesia Stock Excahnge (IDX) in 2011-2014 periods. Based on the result of the research it can concluded that the financial performance (ROA) has signifcant psoitive influence to the firm value (PBV). Corporate social responsibility (CSR) has an impact of the positive influence offinancial performance to the firm value. Good Corporate Governance (KM) has an impact to the positive influence of financial performance to the firm value. Good Corporate Governance (KI) does not haveany impact to the positive influence of financial performance to the firm value.Keywords: Financial Performance, Firm Value, corporate social responsibility, managerial ownership, independent commissioner.